Genistein and enterolactone in relation to Ki-67 expression and HER2 status in postmenopausal breast cancer patients - Jaskulski, Stefanie; Rudolph, Anja; Johnson, Theron S.; Herpel, Esther; Sinn, Peter; Chang-Claude, Jenny (Molecular nutrition & food research, 2017)
Scope Phytoestrogens (PE) may improve breast cancer prognosis by modifying tumor prognostic markers, such as cell proliferation marker Ki-67 and human epidermal growth factor receptor 2 (HER2). Epidemiological evidence linking lignans and isoflavones to Ki-67 and HER2 is limited. We examined associations between the major metabolites of lignans and isoflavones - enterolactone (ENL) and genistein (GEN) - respectively, and Ki-67 expression and HER2 in tumor tissue of breast cancer patients. Methods and results Data from 1060 invasive breast cancer patients from the population-based MARIE study were used. Multivariate-adjusted linear (Ki-67 log-transformed) and quantile regression, and logistic regression analyses (HER2, Ki-67 dichotomized) were performed to calculate β estimates and ORs, respectively. Median post-diagnostic ENL and GEN concentrations were 19.5 and 4.8 nmol/L, respectively. Median Ki-67 was 12.0%, and 21.2% of the tumors were HER2+. After adjustment, there was an inverse association between GEN and Ki-67 at high expression levels (OR for Ki-67 ≥20% versus <20% of 0.93 (95%CI [0.87;0.99]) per 10 nmol/L GEN increment). Conclusion Our findings indicate an inverse association between GEN and Ki-67 at high levels of Ki-67 expression. Additional investigations are recommended to confirm our findings and to further elucidate mechanisms linking PE metabolites to breast cancer survival.
First published: 21 July 2017
Gesehen am 16.08.2018